MTORC2 Activation Mediated by Mesenchymal Stem Cell-Secreted Hepatocyte Growth Factors for the Recovery of Lipopolysaccharide-Induced Vascular Endothelial Barrier. (18th October 2021) - Meng, Shan-Shan; Guo, Feng-Mei; Huang, Li-Li; Huang, Ying-Zi; Xie, Jian-Feng; Yang, Cong-Shan; Qiu, Hai-Bo; Yang, Yi
Abstract : Acute lung injury (ALI)/acute respiratory distress syndrome (ARDS) is characterized by pulmonary microvascular endothelial barrier dysfunction. Mesenchymal stem cell-secreted hepatocyte growth factor (HGF) has positive effects of lipopolysaccharide- (LPS-) induced pulmonary endothelial barrier. Studies have exhibited the mammalian TORC1 (mTORC1) signaling is of potent angiogenesis effects. The mTOR protein kinase has two distinct multiprotein complexes mTORC1 and mTORC2 that regulate different branches of the mTOR network. However, detailed mTORC2 mechanisms of HGF protective effects remain poorly defined. Therefore, the aim of this study was to determine whether mTORC2 mediated protective effects of MSC-secreted HGF against LPS-induced pulmonary microvascular endothelial barrier dysfunction activated like mTORC1 activation. We introduced MSC-PMVEC coculture transwell system and recombinant murine HGF on LPS-induced endothelial cell barrier dysfunction in vitro and then explored potential mechanisms by lentivirus vector-mediated HGF, mTORC1 (raptor), and mTORC2 (rictor) gene knockdown modification. Endothelial paracellular and transcellular permeability, adherent junction protein (VE-Cadherin), cell proliferation, apoptosis, and mTOR-associated proteins were tested. These revealed that HGF could promote quick reestablishment of adherent junction VE-cadherin and decrease endothelial paracellular and transcellular permeability during LSP-induced endothelial dysfunction with the involvement of mTORC2 (rictor) and mTORC1 (raptor) pathways. Raptor and rictor knockdown in LPS-induced PMEVECs with stimulation of HGF increased apoptosis ratio, activated Cleaved-Caspase-3 expression, and downregulated cell proliferation. Moreover, mTORC2/Akt but not mTORC2/PKC had significance on HGF endothelial protective effects. Taken together, these highlight activation mTORC2 pathway could also contribute to vascular endothelial barrier recovery by MSC-secreted HGF in LPS stimulation.